Response of Morphological and Physiological Characters of Patchouli (Pogostemon cablin Benth.) to Water Stress - Sri Nurmayanti; Dimas Prakoswo Widiyani; Adisa Ramadhani Izati (CIB Nusantara, 2025)
Patchouli (Pogostemon cablin Benth.) is a plant that produces essential oils and contributes to Indonesia's foreign exchange. Patchouli plants are very sensitive to water stress and require water as the main ingredient in photosynthesis. This study aims to identify patchouli genotypes resistant to water stress and to determine interactions between patchouli genotypes and field capacity under water stress. The study was conducted at the Plantation Crop Cultivation Practice Garden and Plant Laboratory of Lampung State Polytechnic from October 2023 to March 2024. The method used was a randomized block design (RBD) with a factorial pattern consisting of two factors. Factor 1 is the patchouli genotype, namely G4 = Genotype 4, G5 = Genotype 5, G6 = Genotype 6, and G10 = Comparison clone. Factor 2 watering at field capacity K1 = 60% field capacity, K2 = 80% field capacity, K3 = 100% field capacity, and K4 = 120% field capacity. This study consisted of 16 treatment combinations, each repeated 3 times, for a total of 48 experimental units. The results showed that the patchouli plant genotype had a significant effect only on the observation variable, stover dry weight. Genotypes 4 and 5 were the genotypes that gave the best response to the observation variables of plant height, stem diameter, number of branches, plant water content, leaf area, specific leaf area, and wet weight of the stover. Field capacity had a significant effect on the observation variables, namely plant height, stem diameter, number of branches, leaf turgidity, plant water content, leaf area, specific leaf area, and stover wet weight. In the observation, plant height, number of branches, plant water content, leaf area, specific leaf area, and stover dry weight showed an interaction between the patchouli genotype and the given field capacity.